The impact of macroprudential policies on capital flows in CESEE - Markus Eller; Niko Hauzenberger; Florian Huber; Helene Schuberth; Lukas Vashold (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2021)
In line with the recent policy discussion on the use of macroprudential measures to respond to crossborder risks arising from capital flows, this paper tries to quantify to what extent macroprudential policies (MPPs) have been able to stabilize capital flows in Central, Eastern and Southeastern Europe (CESEE) - a region that experienced a substantial boom-bust cycle in capital flows amid the global financial crisis and where policymakers had been quite active in adopting MPPs already before that crisis. To study the dynamic responses of capital flows to MPP shocks, we propose a novel regimeswitching factor-augmented vector autoregressive (FAVAR) model. It allows to capture potential structural breaks in the policy regime and to control - besides domestic macroeconomic quantities - for the impact of global factors such as the global financial cycle. Feeding into this model a novel intensity-adjusted macroprudential policy index, we find that tighter MPPs may be effective in containing domestic private sector credit growth and the volumes of gross capital inflows in a majority of the countries analyzed. However, they do not seem to generally shield CESEE countries from capital flow volatility.
Keywords: C38; E61; F44; G28; 330; Capital flows; macroprudential policy; global factors; regime switchingFAVAR; CESEE